2019
DOI: 10.1371/journal.pone.0209924
|View full text |Cite
|
Sign up to set email alerts
|

Such a long journey: What health seeking pathways of patients with drug resistant tuberculosis in Mumbai tell us

Abstract: IntroductionThe Indian Tuberculosis (TB) Programme currently faces the dual challenges of tackling increasing numbers of drug resistant (DR) TB cases and regulating practices of a pluralistic private sector catering to TB patients. A study of health seeking behaviour of DR-TB patients in such a situation, offers an opportunity to understand the problems patients face while interacting with health systems.MethodologyForty-six DR-TB patients drawn from 15 high TB burden wards in Mumbai were interviewed using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Previous studies have examined how patients manage their illness and the impact that TB has on their daily lives, their families, and the wider community [19,20], as well as the stigma associated with poverty and HIV and the effects of discrimination [21]. However, defining studies on the experiences of TB patients and their families are not available for all the BRICS countries, and comparison between studies with different methodologies and objectives is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined how patients manage their illness and the impact that TB has on their daily lives, their families, and the wider community [19,20], as well as the stigma associated with poverty and HIV and the effects of discrimination [21]. However, defining studies on the experiences of TB patients and their families are not available for all the BRICS countries, and comparison between studies with different methodologies and objectives is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Patients go and test at other facilities to see if the result is the same. This finding is corroborated by a recent study that looked at health seeking pathways of patients with drug resistant tuberculosis [36]. Courtwright and Turner found that some of the causes of TB stigma were: perceived transmission risk from infected people; poverty; and its association with HIV [37].…”
Section: Discussionmentioning
confidence: 56%
“…Others have to do with the experience of undergoing DR-TB treatment and include psychological distress, economic hardship, and the stigma and discrimination faced by people living with DR-TB, often at the hands of medical providers themselves. The experiential treatment journey of a person who is diagnosed with DR-TB is treacherous at best [32]. High rates of depression and anxiety have been reported among persons undergoing treatment for DR-TB, and while some of this may be due to circumstances faced prior to the DR-TB diagnosis, a substantial proportion of people report worsening of mental health during the first several months of treatment [33].…”
Section: Experiences and Perceptions Of Quality In Dr-tb Carementioning
confidence: 99%